Psychosocial rehabilitation of patients after neurosurgical intervention - K. V. Aymedov; E. A. Grigoryev; S. P. Gorishchek (Journal of Education, Health and Sport, 2015)
The article touches upon the problem of psychosocial rehabilitation of patients after neurosurgical intervention in Ukraine. The authors draw attention to the urgency of this problem in the modern period, since the problem of psychological rehabilitation of neurosurgical patients concerns not only the health care system, the economy, but also the sociocultural aspects. From its solution depends not only the process of recovery of patients, but also their return to normal social and social life. The main research methods were: analysis and synthesis of modern concepts of medical, psychological and social support, treatment, rehabilitation and adaptation of patients undergoing neurosurgical intervention. The main principles of psychosocial support and rehabilitation of patients after neurosurgical intervention are disclosed. The authors point out the need to include psychosocial support during the rehabilitation of patients after neurosurgical intervention. A model of multidisciplinary care for this category of patients has been developed, which is based on a biopsychosocial approach to treatment.